Addressing indigenous health workforce inequities: A literature review exploring 'best' practice for recruitment into tertiary health programmes - Curtis Elana; Wikaire Erena; Stokes Kanewa; Reid Papaarangi (BMC, 2012)
Abstract Introduction Addressing the underrepresentation of indigenous health professionals is recognised internationally as being integral to overcoming indigenous health inequities. This literature review aims to identify 'best practice' for recruitment of indigenous secondary school students into tertiary health programmes with particular relevance to recruitment of Māori within a New Zealand context. Methodology/methods A Kaupapa Māori Research (KMR) methodological approach was utilised to review literature and categorise content via: country; population group; health profession ffocus; research methods; evidence of effectiveness; and discussion of barriers. Recruitment activities are described within five broad contexts associated with the recruitment pipeline: Early Exposure, Transitioning, Retention/Completion, Professional Workforce Development, and Across the total pipeline. Results A total of 70 articles were included. There is a lack of published literature specific to Māori recruitment and a limited, but growing, body of literature focused on other indigenous and underrepresented minority populations. The literature is primarily descriptive in nature with few articles providing evidence of effectiveness. However, the literature clearly frames recruitment activity as occurring across a pipeline that extends from secondary through to tertiary education contexts and in some instances vocational (post-graduate) training. Early exposure activities encourage students to achieve success in appropriate school subjects, address deficiencies in careers advice and offer tertiary enrichment opportunities. Support for students to transition into and within health professional programmes is required including bridging/foundation programmes, admission policies/quotas and institutional mission statements demonstrating a commitment to achieving equity. Retention/completion support includes academic and pastoral interventions and institutional changes to ensure safer environments for indigenous students. Overall, recruitment should reflect a comprehensive, integrated pipeline approach that includes secondary, tertiary, community and workforce stakeholders. Conclusions Although the current literature is less able to identify 'best practice', six broad principles to achieve success for indigenous health workforce development include: 1) Framing initiatives within indigenous worldviews 2) Demonstrating a tangible institutional commitment to equity 3) Framing interventions to address barriers to indigenous health workforce development 4) Incorporating a comprehensive pipeline model 5) Increasing family and community engagement and 6) Incorporating quality data tracking and evaluation. Achieving equity in health workforce representation should remain both a political and ethical priority.